Crowdsourcing-based automated essay scoring framework - Bai, Huanyu (Nanyang Technological University, 2023)
Automated Essay Scoring (AES) is a challenging topic in Natural Language Processing. Although deep learning models achieve remarkable performance for the AES task, they have two major problems. Most AES models are unable to handle the out-of-vocabulary (OOV) words. Besides, training AES models is costly in practice. This thesis aims to handle these two problems.